The Luggage Product Design with Electric Drive Concept - Dian Rafika Sari; Yosef Richo Adrianto; Hardman Budiarjo (Fakultas Industri Kreatif Universitas Surabaya, 2023)
Pro D.I.Y is a combination of Pro (professional) and Do It Yourself (modify or make things yourself) to carry clothes, laptops, skincare, or other loads practically and efficiently. This product will be aimed at influencers/celebs who complain about carrying work items simultaneously but using various sizes of bags. This makes the celebgrams need a personal assistant to help carry the bags. This Portable Bag uses the concept of electric drive which is more efficient to use luggage electrically. This product uses materials that have waterproof properties when exposed to water spills including synthetic leather, aluminum, and parachute cloth. In addition to focusing on the functional side, researchers also focus on design and aesthetic models, to support this, researchers will conduct several data collection techniques so that the resulting product is maximized.